Serological markers of hepatitis B in patients with alcoholic liver disease: a multi-centre survey - Hislop, WS (1981)
In a study of 195 patients derived from five centres in northern Britain and with histologically confirmed alcoholic liver disease we have found an increased prevalence of serological markers of hepatitis B. This increased prevalence was found in each of the five centres; the overall frequency ranged from 11% sero-positivity in fatty liver, 12% in alcoholic hepatitis and 27% in cirrhosis.